2023
DOI: 10.1002/ijgo.14695
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and serum CA19‐9 combined with HE4 are valuable in diagnosing endometriosis‐associated ovarian cancer

Abstract: Objective: Endometriosis-associated ovarian cancer (EAOC) is difficult to diagnose because of its low incidence, uncertain risk factors, and the absence of effective markers. This study aimed to investigate the clinical characteristics of EAOC and identify useful serological markers. Methods:We retrospectively studied the clinical characteristics of patients with EAOC and ovarian endometriosis, obtained between January 1, 2011 and October 31, 2021. Univariate and multivariate logistic regression analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Researchers found clinical characteristics of EAOC differed from those of OEM, such as age at diagnosis older, tumor larger and elevated levels of serum tumor markers (Hermens et al 2020 ; Younis and Izhaki 2023 ; Murakami et al 2020 ). We found that patients with EAOC had elevated serum cancer antigen (CA) 19–9 and human epididymis protein 4 (HE4) in a previous study (Xu et al 2023 ).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Researchers found clinical characteristics of EAOC differed from those of OEM, such as age at diagnosis older, tumor larger and elevated levels of serum tumor markers (Hermens et al 2020 ; Younis and Izhaki 2023 ; Murakami et al 2020 ). We found that patients with EAOC had elevated serum cancer antigen (CA) 19–9 and human epididymis protein 4 (HE4) in a previous study (Xu et al 2023 ).…”
Section: Introductionmentioning
confidence: 73%
“…Chao et al ( 2022 ) discovered that the significance of CA125 and CA19-9 in diagnosing EAOC. Our previous study found that age at diagnosis over 42 years, tumor size over 9.2 cm, and elevated CA19-9 and HE4 levels are risk factors for EAOC (Xu et al 2023 ). In this study, we expanded the population and further validated these findings.…”
Section: Discussionmentioning
confidence: 99%
“…One study suggests that CA 19-9 can be helpful when used alongside CA 125 for the purpose of diagnosing endometriosis and monitoring its treatment [ 29 ]. Another study reports that the combined measurement of CA 19-9 and HE4 may be associated with endometriosis-related ovarian cancer [ 30 ]. Serum CA 19-9 has been shown to be elevated according to clinical stage in patients with endometriosis [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The serum level of CRP in group A was 1.2 g/dL (range, 0.3-16.6), whereas it was 0.3 g/dL (range, 0.3~12.0) in group B, and this difference was also found to be significant (p = 0.000). Regarding the median BMI values, group A had a median of 19.4 kg/m 2 (range, 17-23.4), while group B had a median of 21.5 kg/m 2 (range, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Although these values were significantly different (p = 0.048), it is important to note that both values fell within the normal range of body weight (Table 1).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Xu et al. found that a serum HE4 >59.7 pmol/L could diagnose EAOC, with a specificity of 99.4% when HE4 >140 pmol/L ( 68 ). For epithelial ovarian cancer, the combined detection of HE4 and CA125 demonstrates higher sensitivity than CA125 alone.…”
Section: Clinical Diagnosis Of Eaocmentioning
confidence: 99%